Preparation and use of a high-carbon high-alloy steel isothermal quenching structure etchant

By preparing isothermal quenching tissue corrosion agent of high-carbon high alloy steel, and using a mixture of nitric acid alcohol and heavy sodium sulfite for corrosion, the problems of picric acid disable and nitric acid alcohol corrosion agent in the prior art are solved, and efficient and safe metallographic phase is achieved Observation and evaluation reveal the obvious morphology of each phase.

CN114113086BActive Publication Date: 2025-01-14AVIC HARBIN BEARING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111341720.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-12
Publication Date
2025-01-14
Estimated Expiration
2041-11-12

AI Technical Summary

Technical Problem

Pictic acid is prohibited in existing Lepera corrosion agents, and nitric acid alcohol corrosion agents are difficult to efficiently and accurately display the metallographic structure after isothermal quenching of high-carbon and high-alloy steel, which affects the evaluation of heat treatment process parameters.

Method used

Prepare a high-carbon and high-alloy steel isothermal quenching tissue corrosion agent, and realize droplets by placing a mixture of 4% to 10% nitric acid alcohol solution and 0.5% to 1% squite sodium sulfite solution for wire cutting, grinding and corrosion samples. Erosion or soak corrosion, followed by observation with a metallographic microscope.

Benefits of technology

It provides a safe, low-cost, pollution-free high-efficiency metallographic corrosion agent, which can show ideal tissue morphology within 25 seconds, and has obvious contrast between phases. It is suitable for efficient observation of isothermal quenching structures of high-carbon and high-alloy steel and evaluate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114113086B_ABST
    Figure CN114113086B_ABST
Patent Text Reader

Abstract

A method for preparing and using a high-carbon high-alloy steel isothermal quenching structure etchant, which belongs to the field of analysis and testing. It solves the problem that the existing Lepera etchant raw material picric acid is prohibited, and the conventional nitric acid alcohol etchant is difficult to efficiently and accurately etch and display the metallographic structure of high-carbon high-alloy steel after isothermal quenching. Preparation: A nitric acid alcohol solution with a volume fraction of 4% to 10% is mixed with a sodium metabisulfite solution with a mass fraction of 0.5% to 1%. Use: 1. Wire cutting sample preparation; 2. Grinding and polishing sample preparation; 3. Sample corrosion; 4. Metallographic structure observation. The present invention has low cost, convenient and safe operation, and no pollution; under the premise of ensuring safety, the etchant is used to achieve efficient and accurate observation, analysis and evaluation of the isothermal quenching structure of high-carbon high-alloy steel, so as to further evaluate the effectiveness of the isothermal quenching process; when used, it only takes 25 seconds to obtain an ideal tissue morphology. The present invention is suitable for metallographic etching of the isothermal quenching structure of high-carbon high-alloy steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of analysis and testing, and in particular relates to a preparation and use method of a high-carbon high-alloy steel isothermal quenching tissue corrosive agent. Background Art

[0002] The austempering heat treatment process is usually to obtain a composite structure of martensite and lower bainite to meet the material's requirements for strength and toughness. Therefore, lower bainite austempering is currently a commonly used metal toughening process for high-carbon high-alloy steel. In order to evaluate the quality of the austempering process, it is usually necessary to observe and analyze the metallographic structure after quenching.

[0003] Lepera reagent is a commonly used corrosive agent for observing the metallographic structure after isothermal quenching. The corrosive agent is composed of a 1:1 sodium metabisulfite aqueous solution (10g / L) and a picric acid ethanol solution (40g / L). Even the improved Lepera corrosive agent usually contains a picric acid solution. Picric acid, also known as trinitrophenol, is currently prohibited from use in laboratories due to its hazards to human health, the environment, etc., and as the main raw material of TNT explosives. Nitric acid alcohol is currently the most common corrosive agent, but its corrosion effect on the microstructure (martensite, bainite and carbide, etc.) after isothermal quenching is not ideal. Therefore, it is difficult for existing commonly used corrosive agents to achieve efficient and accurate corrosion of the isothermal quenching structure of high-carbon high-alloy steel, which directly affects the evaluation of heat treatment process parameters. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that the raw material of the existing Lepera corrosive agent, picric acid, is prohibited, and the conventional nitric acid alcohol corrosive agent is difficult to efficiently and accurately corrode and display the metallographic structure of high-carbon high-alloy steel after isothermal quenching, and to provide a preparation and use method of a high-carbon high-alloy steel isothermal quenching structure corrosive agent.

[0005] A method for preparing a high-carbon high-alloy steel isothermal quenching structure corrosive agent, which is achieved by the following steps:

[0006] 1. Prepare a 4% to 10% nitric acid alcohol solution by volume, and then prepare a 0.5% to 1% sodium metabisulfite solution by mass;

[0007] 2. The above-mentioned nitric acid alcohol solution and sodium metabisulfite solution are mixed in a volume ratio of 1 mL: (0.2-1) mL to obtain a high-carbon high-alloy steel isothermal quenching tissue corrosive agent, thereby completing the preparation method.

[0008] The above-mentioned method for using the high-carbon high-alloy steel isothermal quenching structure corrosive agent is implemented according to the following steps:

[0009] 1. Wire cutting sample preparation: Use wire cutting equipment to wire cut high-carbon high-alloy steel isothermal quenching parts or samples that need metallographic structure observation. According to the subsequent grinding and polishing sample preparation requirements, set the size of the sample to obtain the wire-cut sample;

[0010] 2. Grinding and polishing: Use a pre-grinder or a fully automatic grinder and polisher to grind, polish, clean and dry the above-mentioned wire-cut samples to obtain mirror-surface samples;

[0011] 3. Sample corrosion: Use high-carbon high-alloy steel isothermal quenching tissue corrosive agent to corrode the above mirror sample, using drip corrosion or immersion corrosion. After the corrosion is completed, rinse with running water immediately, then rinse with anhydrous ethanol, and then blow dry to obtain a metallographic sample;

[0012] 4. Metallographic structure observation: Observe and analyze the metallographic samples using a metallographic microscope to obtain the microstructure morphology of the high-carbon high-alloy steel after isothermal quenching, thereby completing the method of use.

[0013] The advantages of the present invention are:

[0014] The high-carbon high-alloy steel isothermal quenching tissue corrosive agent prepared by the invention does not use prohibited ingredients, is simple to prepare, has low cost, is convenient and safe to operate, is easy to control, and is pollution-free.

[0015] The invention solves the shortcomings of existing corrosive agents and proposes a preparation and use method of a metallographic corrosive agent with high efficiency, good effect and high safety. Under the premise of ensuring safety, the corrosive agent is used to realize efficient and accurate observation, analysis and evaluation of the isothermal quenching structure of high-carbon high-alloy steel, so as to further evaluate the effectiveness of the isothermal quenching process.

[0016] When the etchant of the present invention is used, an ideal microstructure morphology can be obtained in only 25 seconds. After being etched by the etchant of the present invention, the contrast between the phases is more obvious, wherein the carbide is bright white, the "short rod-shaped" bainite is black, the needle-shaped martensite is brown, and part of the grain boundary martensite is blue.

[0017] The invention is suitable for metallographic etching of isothermal quenching structure of high-carbon high-alloy steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a metallographic microstructure of the 18Cr4Mo4V high carbon high alloy steel in the embodiment after being treated by isothermal quenching process 1 and then etched by corrosive agent for 25 seconds;

[0019] Figure 2 This is a metallographic microstructure of the 18Cr4Mo4V high carbon high alloy steel in the embodiment after being treated by isothermal quenching process 2 and then etched by corrosive agent for 25 seconds;

[0020] Figure 3This is a metallographic microstructure of the 18Cr4Mo4V high carbon high alloy steel in the embodiment after being treated by isothermal quenching process 1 and the comparison group after immersion corrosion for 3 minutes;

[0021] Figure 4 This is a metallographic microstructure of the 18Cr4Mo4V high carbon high alloy steel in the embodiment after being treated by isothermal quenching process 1 and the comparison group after immersion corrosion for 8 minutes;

[0022] Figure 5 This is a metallographic microstructure of the 18Cr4Mo4V high carbon high alloy steel in the embodiment after being treated by isothermal quenching process 2 and the comparison group after immersion corrosion for 3 minutes;

[0023] Figure 6 This is a metallographic microstructure diagram of the 18Cr4Mo4V high carbon high alloy steel in the embodiment after being treated by isothermal quenching process 2 and the control group being immersed in corrosion for 8 minutes. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0025] Specific implementation method 1: This implementation method is a method for preparing a high-carbon high-alloy steel isothermal quenching structure corrosive agent, which is implemented by the following steps:

[0026] 1. Prepare a 4% to 10% nitric acid alcohol solution by volume, and then prepare a 0.5% to 1% sodium metabisulfite solution by mass;

[0027] 2. The above-mentioned nitric acid alcohol solution and sodium metabisulfite solution are mixed in a volume ratio of 1 mL: (0.2-1) mL to obtain a high-carbon high-alloy steel isothermal quenching tissue corrosive agent, thereby completing the preparation method.

[0028] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that in step 1, a nitrate alcohol solution with a volume fraction of 8% is prepared, and then a sodium metabisulfite solution with a mass fraction of 0.7% is prepared. The rest is the same as specific implementation method 1.

[0029] Specific implementation method three: This implementation method is different from specific implementation method one in that in step two, the nitric acid alcohol solution and the sodium metabisulfite solution are mixed in a volume ratio of 1 mL:0.8 mL. The rest is the same as specific implementation method one.

[0030] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the nital alcohol solution in step 1 is prepared by pouring anhydrous ethanol into a beaker, and then adding concentrated nitric acid with a mass fraction of 68% under stirring to prepare a nital alcohol solution with a volume fraction of 4% to 10%. The other steps and parameters are the same as those of specific embodiments 1 to 3.

[0031] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the sodium metabisulfite solution in step 2 is configured as follows: the solute is sodium metabisulfite and the solvent is distilled water. The other steps and parameters are the same as those of specific embodiments 1 to 4.

[0032] Specific implementation method 6: In this implementation method, the above-mentioned method of using the high-carbon high-alloy steel isothermal quenching structure corrosive agent is implemented according to the following steps:

[0033] 1. Wire cutting sample preparation: Use wire cutting equipment to wire cut high-carbon high-alloy steel isothermal quenching parts or samples that need metallographic structure observation. According to the subsequent grinding and polishing sample preparation requirements, set the size of the sample to obtain the wire-cut sample;

[0034] 2. Grinding and polishing: Use a pre-grinder or a fully automatic grinder and polisher to grind, polish, clean and dry the above-mentioned wire-cut samples to obtain mirror-surface samples;

[0035] 3. Sample corrosion: Use high-carbon high-alloy steel isothermal quenching tissue corrosive agent to corrode the above mirror sample, using drip corrosion or immersion corrosion. After the corrosion is completed, rinse with running water immediately, then rinse with anhydrous ethanol, and then blow dry to obtain a metallographic sample;

[0036] 4. Metallographic structure observation: Observe and analyze the metallographic samples using a metallographic microscope to obtain the microstructure morphology of the high-carbon high-alloy steel after isothermal quenching, thereby completing the method of use.

[0037] In step three of this embodiment, the process is immediately rinsed with running water in order to remove the remaining high-carbon high-alloy steel isothermal quenching structure corrosive agents.

[0038] Specific implementation method 7: This implementation method is different from specific implementation method 6 in that a pre-grinder is used in step 1: 240# sandpaper, 400# sandpaper, 800# sandpaper, 1000# sandpaper, 1500# sandpaper, and ≤3μm diamond polishing agent are used to grind and polish the sample after wire cutting. Other steps and parameters are the same as those of specific implementation method 6.

[0039] Specific embodiment eight: This embodiment differs from specific embodiment six or seven in that in step one, a fully automatic grinding and polishing machine is used: the sample is mounted according to the aperture of the automatic grinding and polishing disc, and then a suitable grinding and polishing machine program is selected for sample preparation, and the final suspension size must be ensured to be ≤3μm. The other steps and parameters are the same as those of specific embodiment six or seven.

[0040] Specific embodiment 9: This embodiment is different from specific embodiments 6 to 8 in that, in step 1, cleaning and drying are performed by rinsing with water and then spraying and drying with anhydrous ethanol. The other steps and parameters are the same as those of specific embodiments 6 to 8.

[0041] Specific embodiment 10: This embodiment differs from specific embodiments 6 to 9 in that if drip etching is used in step 3, the drip etching time is 5s to 120s; if immersion etching is used, the immersion time is 5s to 30s. Other steps and parameters are the same as those of specific embodiments 6 to 9.

[0042] The beneficial effects of the present invention are verified by the following examples:

[0043] Example:

[0044] A method for preparing a high-carbon high-alloy steel isothermal quenching structure corrosive agent, which is achieved by the following steps:

[0045] 1. Prepare a 10% nitric acid alcohol solution by volume, and then prepare a 1% sodium metabisulfite solution by mass;

[0046] 2. The above-mentioned nitric acid alcohol solution and sodium metabisulfite solution are mixed in a volume ratio of 1 mL:0.8 mL to obtain a high-carbon high-alloy steel isothermal quenching tissue corrosive agent to complete the preparation method.

[0047] The preparation of the nital alcohol solution in step 1 of this embodiment is as follows: 180 mL of anhydrous ethanol is poured into a 300 mL beaker, and then 20 mL of concentrated nitric acid with a mass fraction of 68% is added under stirring to prepare a nital alcohol solution with a volume fraction of 10%.

[0048] Preparation of the sodium metabisulfite solution in step 2 of this embodiment: 2 g of sodium metabisulfite was weighed using an electronic balance and filter paper, poured into a 250 mL beaker, and then 198 mL of distilled water was added, and stirred thoroughly with a glass rod to dissolve, to prepare a sodium metabisulfite solution with a mass fraction of 1%.

[0049] The method for using the high-carbon high-alloy steel isothermal quenching structure corrosive agent prepared by the above method is implemented by the following steps:

[0050] 1. Wire cutting sample preparation: Use wire cutting equipment to wire cut high-carbon high-alloy steel isothermal quenching parts or samples that need metallographic structure observation. According to the subsequent grinding and polishing sample preparation requirements, set the size of the sample to obtain the wire-cut sample;

[0051] 2. Grinding and polishing: Use a pre-grinder or a fully automatic grinder and polisher to grind, polish, clean and dry the above-mentioned wire-cut samples to obtain mirror-surface samples;

[0052] 3. Sample corrosion: Use high-carbon high-alloy steel isothermal quenching tissue corrosive agent to corrode the above mirror sample, using drip corrosion or immersion corrosion. After the corrosion is completed, rinse with running water immediately, then rinse with anhydrous ethanol, and then blow dry to obtain a metallographic sample;

[0053] 4. Metallographic structure observation: Observe and analyze the metallographic samples using a metallographic microscope to obtain the microstructure morphology of the high-carbon high-alloy steel after isothermal quenching, thereby completing the method of use.

[0054] The operation of this embodiment is as follows:

[0055] 8Cr4Mo4V high carbon high alloy bearing steels treated by two different austempering processes were sampled by wire cutting, and Φ12×15mm samples were taken;

[0056] Two different isothermal quenching processes are process 1: 1105℃ insulation for 30min, followed by isothermal quenching in a 200℃ salt bath for 2h; process 2: 1120℃ insulation for 30min, followed by isothermal quenching in a 200℃ salt bath for 2h.

[0057] The samples were mounted using a Φ30 mm cold mounting mold and metallographic mounting materials. Then, the samples were polished using an automatic polishing machine (Tegramin-25, Struers). The program was set to use 9 μm, 3 μm and 1 μm suspensions in sequence. After polishing, the samples were rinsed with running water and anhydrous ethanol in sequence and dried to obtain mirror-surface samples.

[0058] Austempered structure etchant for high carbon high alloy steel: 10 mL of 10% nitric acid alcohol solution and 8 mL of 1% sodium metabisulfite solution are poured into a 25 mL beaker in sequence and stirred thoroughly to obtain a mixed etchant;

[0059] Use a rubber-tipped dropper to take the mixed etchant and quickly cover the surface of the mirror sample, perform drop etching, and keep it for 25 seconds, then rinse it with running water and anhydrous ethanol, and blow it dry to obtain a metallographic sample;

[0060] Under the condition that the parameters of other steps remain unchanged, in order to contrast with the traditional nitric acid alcohol corrosion effect, the samples under the same process were immersed and corroded using the configured 10% nitric acid alcohol solution to obtain metallographic samples (marked as the control group).

[0061] The metallographic microscopy (NIM-910, Nanjing Yongxin Company) was used to observe and analyze the metallographic structures of the above metallographic samples. The magnification was 1000 times to obtain the morphology of the Mapei composite microstructure after isothermal quenching of high-carbon high-alloy steel.

[0062] Results, such as Figure 1 As shown, it can be seen that after the 8Cr4Mo4V high-carbon high-alloy steel in this embodiment is treated by isothermal quenching process 1, when the etchant of this embodiment is used, it only takes 25 seconds to obtain the ideal microstructure morphology. It can be seen that after being etched by the etchant of the present invention, the contrast between the phases is more obvious, among which the carbide is bright white, the "short rod-shaped" bainite is black, the needle-shaped martensite is brown, and part of the grain boundary martensite is blue.

[0063] The results of the control group are as follows: Figure 3 and Figure 4 As shown, it can be seen that when immersed in corrosion for 3 minutes ( Figure 3 As shown in the figure), only relatively clear grain boundaries can be seen, and the carbide contrast is similar to that of the matrix; when the corrosion time is extended to 8 minutes ( Figure 4 As shown in the figure, it can be seen that there is "short rod-shaped" bainite inside the grains, and no martensite structure has been corroded.

[0064] The 8Cr4Mo4V steel treated by isothermal quenching process 2 was corroded by the corrosive agent of this embodiment and 10% nitric acid alcohol, and the results are shown in the attached figure. Figure 2 , Figure 5 and Figure 6 shown by Figure 2 It can be seen that after etching with the etchant of this embodiment, the contrast between the phases is quite obvious, wherein the carbide is bright white, the "short rod-shaped" bainite is black, and the needle-shaped martensite is brown.

[0065] The 8Cr4Mo4V steel treated by the same process was corroded by 10% nitric acid alcohol. The results of the control group are as follows: Figure 5 and Figure 6 As shown; it can be seen that when immersed in corrosion for 3 minutes ( Figure 5 As shown in Figure 1, only relatively clear grain boundaries can be seen. The same as process 1 is that the carbide contrast is similar to the matrix. When the corrosion time is extended to 8 minutes ( Figure 6 As shown in the figure, it can be seen that there is "short rod-shaped" bainite inside the grains, and no martensite structure has been corroded.

Claims

1. A method for using a high-carbon high-alloy steel isothermal quenching structure corrosive agent, characterized in that The usage is implemented by following the steps below: ① Wire cutting sample preparation: Use wire cutting equipment to wire cut high-carbon high-alloy steel isothermal quenching parts or samples that need metallographic structure observation. According to the subsequent grinding and polishing sample preparation requirements, set the size of the sample to obtain the wire-cut sample; ② Grinding and polishing sample preparation: Use a pre-grinder or a fully automatic grinder and polisher to grind, polish, clean and dry the above-mentioned wire-cut samples to obtain mirror-surface samples; ③. Sample corrosion: Use high-carbon high-alloy steel isothermal quenching tissue corrosive agent to corrode the above-mentioned mirror sample, using drip corrosion or immersion corrosion. After the corrosion is completed, rinse with running water immediately, then rinse with anhydrous ethanol, and then blow dry to obtain a metallographic sample; ④. Metallographic structure observation: Observe and analyze the metallographic sample using a metallographic microscope to obtain the microstructure morphology of the high-carbon high-alloy steel after isothermal quenching, and complete the method of use; If drip etching is used in step ③, the drip etching time is 5s~120s; if immersion etching is used, the immersion time is 5s~30s; In step ②, a fully automatic grinding and polishing machine is used: the sample is mounted according to the aperture of the automatic grinding and polishing disc, and then a suitable grinding and polishing machine program is selected for sample preparation, and the final suspension size must be ensured to be ≤3μm; Cleaning and drying in step ②: rinse with water and then spray with anhydrous ethanol to dry; In step ②, a pre-grinder is used to grind and polish the wire-cut sample using 240# sandpaper, 400# sandpaper, 800# sandpaper, 1000# sandpaper, 1500# sandpaper, and ≤3μm diamond polishing agent in sequence; The high carbon high alloy steel to be subjected to metallographic structure observation in step ① is 8Cr4Mo4V high carbon high alloy bearing steel; The high carbon high alloy steel isothermal quenching structure corrosive agent is prepared according to the following steps:

1. Prepare a 10% nitric acid alcohol solution by volume, and then prepare a 1% sodium metabisulfite solution by mass; 2. Mix the above-mentioned nitric acid alcohol solution and sodium metabisulfite solution in a volume ratio of 1 mL:0.8 mL to obtain a high-carbon high-alloy steel isothermal quenching tissue corrosive agent.

2. The method for using a high carbon high alloy steel isothermal quenching structure corrosive agent according to claim 1, characterized in that Preparation of the nital alcohol solution in step 1: Pour anhydrous ethanol into a beaker, and then add concentrated nitric acid with a mass fraction of 68% while stirring to prepare a nital alcohol solution with a volume fraction of 4% to 10%.

3. The method for using a high-carbon high-alloy steel isothermal quenching structure corrosive agent according to claim 1, characterized in that The preparation of the sodium metabisulfite solution in step 2 is as follows: the solute is sodium metabisulfite and the solvent is distilled water.

Citation Information

Patent Citations

  • Qualitative identification method of metallographic structure of austempered bainite steel

    CN109470538A